Technology and Manufacturing Process Selection The Product Life Cycle Perspective - Henriques, Elsa.; Pecas, Paulo; Silva, Arlindo; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2014)
This book provides specific topics intending to contribute to an improved knowledge on Technology Evaluation and Selection in a Life Cycle Perspectives. Although each chapter will present possible approaches and solutions, there are no recipes for success. Each reader will find his/her balance in applying the different topics to his/her own specific situation. Case studies presented throughout will help in deciding what fits best to each situation, but most of all any ultimate success will come out of the interplay between the available solutions and the specific problem or opportunity the reader is faced with.
Material flow cost accounting -- Life Cycle based Evaluation and Interpretation of Technology Chains in Manufacturing -- Selecting manufacturing process chains in the early stage of the product engineering process with focus on energy consumption -- Manufacturing with Minimal Energy Consumption -- Integrated framework for life cycle-oriented evaluation of product and process technologies.
Keywords: Engineering; Industrial engineering; Engineering economy; Engineering; Industrial and Production Engineering; Engineering Economics, Organization, Logistics, Marketing; Transportation